Pozycja ustrojowa Sądu Najwyższego Stanów Zjednoczonych - Machaj, Łukasz (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The article briefly analyzes the position of the Supreme Court of the United States within the American political-and-legal system. The author concisely describes the Court’s modus operandi, considers its relations with legislative (majoritarian) branche of government in the context of the doctrine of separation and balance of powers and reflects on the notions of „judicial activism” and „judicial restraint”. In conclusion the author observes that even though the Supreme Court is actively engaged in political disputes, its status remains a function of the American model of constitutional democracy and its authority is not going to be jeopardized in a predictable future.
Keywords: judicial activism; judicial restraint; The United States’ Supreme Court; Marbury v. Madison; separation of powers